CAPACIDAD DE DIFUSIÓN DEL IÓN CALCIO A TRAVÉS DE LA DENTINA RADICULAR UTILIZANDO CUATRO TIPOS DE VEHÍCULOS: ANESTESIA, HIDRÓXIDO DE CALCIO CALCIFAR®, GLICERINA Y POLIETILENGLICOL (2018)
Objective: To determine the capacity of diffusion of the calcium ion through the radicular dentine using four vehicles: Anaesthesia, liquid calcium hydroxide, Calcifar®, glycerin and polyethilglycol.Materials and methods: The specimens were randomly grouped. Twenty teeth were filled with calcium hydroxide in paste mixed with aqueous calcium hydroxide (Calcifar®), 20 with anaesthesia, 20 with glycerin, 20 with polyethilglycol, 5 were filled with Ultracal and 5 were left with no treatment. The crowns of the teeth were eliminated, prepared with CROWN-DOWN biomechanical technique, EDTA (RCprep) was used and irrigated with NaOCl at 5.25%. They were dried with paper points and filled with calcium hydroxide then divided into 4 experimental groups and 1 control group. They were immersed in to 2 ml of sterile distilled water, to make measures of the ion calcium concentration with the colorimeter method using a spectrophotometer in different periods of time at day 1, 5, 15, 30.Results: The greatest degree of calcium ion diffusion was obtained the first day which diffused 39.6mg/dl; with comparisons made between period of time in relation with the vehicle, the anaesthesia group had 39.6 ± 26.4, calcium hydroxide liquid 32.4mg/dl ± 41.3 and the glycerin group with 37.5mg/dl ± 36.9. Diffusion decreased from the fifth day. In all periods of time the vehicle that presented the highest liberation was the group of calcium ion with anaesthesia and the lowest liberation rate was given by the polyethilglycol which was constant during the periods of time analyzed.Conclusions: The best vehicle for calcium hydroxide ion was anaesthesia. The viscous vehicles demonstrated they can maintain constant liberation of calcium ions through the period of time measured.